Influence of propylene glycol on conception rate in cows - ERISIR, ZEKI; YILDIZ, ATILLA (The Indian Journal of Animal Sciences, 2016)
The aim of the study was to evaluate effect of propylene glycol (PG) drenched during the first 7 days after fixed-time artificial insemination (FTAI) on plasma progesterone (P4) and insulin levels, and on pregnancy rate in Holstein cows in summer. Ovsynch program was performed in 40 healthy Holstein cows. Cows were distributed randomly into two groups as propylene glycol (group PG) (20) and control group (group C) (20). Group PG and group C were daily administered with 500 ml of PG and water , respectively for 7 days from day 0 to 7 post insemination. Pregnancy diagnosis was carried out 60 days after insemination via rectal examination. Cows exposed to moderate heat stress due to temperature-humidity index (74.4 ± 1.9 mean THI). Conception rate for cows in group PG increased 2.9 fold when was compared with group C. On day 7, the insulin levels were higher in group PG than group C. It was concluded that PG administered once daily from day 0 to 7 after FTAI increased insulin and P4 concentrations and the conception rate in Holstein cows. The rise in insulin and P4 levels depending on the drenched PC are likely related with the increases of conception rate.